Histopathological study of non neoplastic lesion in cervix at Birat Medical College Teaching Hospital Nepal - Jha, Krishna Kumar; Singh, Mrinalini (Journal of Chitwan Medical College, 2018)
Introduction: Like in other developing countries non –neoplastic region of cervix in pap smear is most common findings. In Nepal... In Nepal cervical pap-smear screening is not done my most of woman due to lack of awareness. The objective of this study is to find the prevalence of non-neoplastic lesion of cervix. Methods: This was a retrospective study of 486 conventional cervical Pap smears reported from the Department of Pathology. The time period was from March 2015 to May 2018. We used Bethesda system to report our all our slides. All the cases were reviewed by consultant pathologist of Birat medical college. This research is done according to rule of BMCTH. Results: Total cases were 486 in two years period in which 456 cases were satisfactory for evaluation and 30 cases were unsatisfactory for evaluation which is due to thick neutrophilic exudates, mucous, degenerative cells and hemorrhage. The age of the patients ranged from 20 to 80 years with an average age of 35.5 years. Non specific inflammatory smear is 440 that is 90.53%, Bacterial vaginosis is 10 that is 2.05%, Candidiasis is 04 that is 0.82% and trichomonas vagenalis is 02 that is 0.41%. Conclusion: Simple screening test like cervical papanicolaou smear (Pap)can detect the non-neoplastic lesion of cervix. If non-neoplatic lesion of cervix is not treated as soon as possible than the chances of being infertility, salpingitis and even neoplasia is more. So non-neoplastic lesion of cervix is as important as neoplastic lesion of cervix.